Biblia sakramentem miłości Boga i Kościoła - Bardski, Krzysztof (Verbum Vitae, 2005)
In the christian antiquity the word sacrament designated any sacred sign. The Bible can be considered as a sign of the love between God and the Church. In our article we analyze the symbols created in connection with the more-than-literal interpretation ofthe Song of Songs. The different aspects o f the loving relation between the Bridegroom and the Bride have been interpreted by the ancient and medieval commentators in the light of the role that the Bible plays in the relation between Jesus and the Church or Jesus and the human soul.